Comprehensive Physiology 2018
DOI: 10.1002/cphy.c170055
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like Peptide‐2 and the Regulation of Intestinal Growth and Function

Abstract: Glucagon-like peptide-2 (GLP-2) is an intestinally derived hormone that enhances intestinal growth, digestion, absorption, barrier function, and blood flow in healthy animals as well as preventing damage and improving repair in preclinical models of enteritis and colitis and following massive small bowel resection. These beneficial effects of GLP-2 on the intestinal tract are largely recapitulated in humans with intestinal failure. The high-specificity of this peptide for the intestinal tract and the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 381 publications
2
74
0
Order By: Relevance
“…The role of the IGF‐1R in CD36 expression was also confirmed in the human intestinal epithelial Caco‐2BBE cells in vitro. These findings are consistent with the known requirement for both IGF‐1 and the IE‐IGF‐1R in the intestinotrophic functions of GLP‐2 19 . The involvement of the IE‐IGF‐1R in the enterocyte lipid signaling pathway is also not surprising, as insulin stimulates the translocation of CD36 from endosomes to the plasma membrane in cardiomyocytes 45 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The role of the IGF‐1R in CD36 expression was also confirmed in the human intestinal epithelial Caco‐2BBE cells in vitro. These findings are consistent with the known requirement for both IGF‐1 and the IE‐IGF‐1R in the intestinotrophic functions of GLP‐2 19 . The involvement of the IE‐IGF‐1R in the enterocyte lipid signaling pathway is also not surprising, as insulin stimulates the translocation of CD36 from endosomes to the plasma membrane in cardiomyocytes 45 .…”
Section: Discussionsupporting
confidence: 84%
“…In addition to diet, other modulators of the intestinal lipid processing pathway are known. For example, glucagon‐like peptide‐2 (GLP‐2) is an intestinotrophic hormone that is endogenously secreted by the intestinal enteroendocrine L cell in response to fat ingestion and which, following exogenous administration, increases postprandial lipid absorption through enhanced CD36 glycosylation, leading to increased CM assembly and secretion 19,20 . However, the precise mechanism underlying this effect is still unclear, as the GLP‐2 receptor is not located on the enterocytes,21‐23 thus necessitating the actions of downstream mediators.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 and GLP-2 are secreted in response to ingested nutrients, including glucose and fat, and their main biological actions are to enhance insulin secretion and intestinal epithelial growth, respectively 19 . The growth-stimulating effects of GLP-2 accompany nutrient ingestion and result from both increased epithelial proliferation and decreased apoptosis 20 . GLP-2 also enhances nutrient digestion and absorption, increases intestinal transit time, increases intestinal blood flow, improves epithelial barrier function, and enhances immune protection by increasing Paneth cell function.…”
Section: Paracrine Actions Of Eecsmentioning
confidence: 99%
“…Despite the prominent effects of GLP-2 on the intestinal epithelium, these actions appear to be indirect because GLP-2 receptors are not expressed on intestinal stem cells (either Lgr5+ crypt base or in Bmi1+ cells that comprise the proliferative reserve stem cell population) 20 . Although GLP-2 receptors are expressed almost exclusively in the gastrointestinal tract, they are found on 3 distinct cell types, but not intestinal epithelial cells.…”
Section: Paracrine Actions Of Eecsmentioning
confidence: 99%
“…GLP-2 exerts its functions through the 7-transmembrane G protein coupled GLP-2 receptor (GLP-2R) and the expression of GLP-2R is largely confined to gastrointestinal tract, with the highest level in the jejunum (i.e. jejunum > duodenum/ileum > colon > stomach) 7 . Studies have shown that intestinal crypt epithelial cell and intestinal villus epithelial cells do not express the GLP-2R, while intestinal stromal cell (such as intestinal subepithelial myofibroblasts, ISEMFs) do express GLP-2R.…”
Section: Introductionmentioning
confidence: 99%